A Tunable 3D Nanostructured Conductive Gel Framework Electrode for High‐Performance Lithium Ion Batteries. Issue 22 (22nd March 2017) - Shi, Ye; Zhang, Jun; Bruck, Andrea M.; Zhang, Yiman; Li, Jing; Stach, Eric A.; Takeuchi, Kenneth J.; Marschilok, Amy C.; Takeuchi, Esther S.; Yu, Guihua
Abstract : This study develops a tunable 3D nanostructured conductive gel framework as both binder and conductive framework for lithium ion batteries. A 3D nanostructured gel framework with continuous electron pathways can provide hierarchical pores for ion transport and form uniform coatings on each active particle against aggregation. The hybrid gel electrodes based on a polypyrrole gel framework and Fe3 O4 nanoparticles as a model system in this study demonstrate the best rate performance, the highest achieved mass ratio of active materials, and the highest achieved specific capacities when considering total electrode mass, compared to current literature. This 3D nanostructured gel‐based framework represents a powerful platform for various electrochemically active materials to enable the next‐generation high‐energy batteries. Abstract : A tunable 3D nanostructured gel framework with continuous electron pathways can provide hierarchical pores for ion transport and form uniform coatings on each active particle against aggregation. The hybrid gel electrodes based on a polypyrrole gel framework and Fe3 O4 nanoparticles demonstrate one of the best rate performances and the highest achieved specific capacities when considering total electrode mass.